2007
DOI: 10.1001/archpsyc.64.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Differential Adult Health Burden by Conduct Problem Subtypes in Males

Abstract: Context: A cardinal feature of the DSM-IV diagnostic criteria for conduct disorder is the distinction between childhood-vs adolescent-onset subtypes. Whether such developmental subtypes exist in the population and have different prognoses should be rigorously tested to inform the DSM-V.Objectives: To evaluate the epidemiological validity of childhood-vs adolescent-onset conduct problems in a prospective birth cohort, and to assess whether life-coursepersistent conduct problems are associated with a greater adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
331
8
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(370 citation statements)
references
References 65 publications
27
331
8
4
Order By: Relevance
“…Our findings support suggestions that full recovery from conduct problems rarely occurs [2] and contradict the notion that CL individuals should be indistinguishable from typical individuals in adulthood [21]. Some have suggested that the decrease in problem behaviours in CL youth may occur in parallel with the development of "off-putting" personality characteristics, such as social awkwardness and social anxiety [17]. Our results do not support this hypothesis, in that CL individuals were not at higher risk of internalising problems compared to the EOP or AO trajectories examined in the present work.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our findings support suggestions that full recovery from conduct problems rarely occurs [2] and contradict the notion that CL individuals should be indistinguishable from typical individuals in adulthood [21]. Some have suggested that the decrease in problem behaviours in CL youth may occur in parallel with the development of "off-putting" personality characteristics, such as social awkwardness and social anxiety [17]. Our results do not support this hypothesis, in that CL individuals were not at higher risk of internalising problems compared to the EOP or AO trajectories examined in the present work.…”
Section: Discussionsupporting
confidence: 63%
“…Early risk factors such as harsh parenting, maternal anxiety, parental instability, and partner cruelty to mother but also mother and child diet have shown to be associated with the EOP trajectory [12,13], as well as adolescence correlates such as peer problems, emotional difficulties, and high risk of affiliating with deviant peers [14,15]. Early risk factors also account for AO individuals, particularly parental instability [16], low IQ and under controlled temperament [17]. Concomitant risk factors in adolescents with conduct problems include high-risk sexual behaviour, high levels of academic difficulties, and substance use [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best GMM applications are motivated by strong taxonomic theories and include construct validation analyses to increase confidence in the obtained trajectory classes (e.g., Odgers et al, 2007). Often, however, there is little theoretical justification for the existence of discrete groups.…”
Section: Theoretical Concernsmentioning
confidence: 99%
“…Numerous studies have shown that LCP begins in childhood and there has been the general assumption that the key driving force lies in an unusually early age of onset. Her trajectory analyses are critically important in showing that childhood-limited (CL) antisocial behaviour is very common, with only a third going on to follow an LCP path (Odgers et al 2007a). The key question is what drives the persistence into adult life.…”
Section: Introductionmentioning
confidence: 99%